1992
DOI: 10.1002/app.1992.070440308
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐radiation induced graft‐copolymerization of hydroxyethyl methacrylate onto cotton cellulose

Abstract: SYNOPSISTwo-hydroxyethyl methacrylate was grafted onto cotton cellulose using photoinitiation technique in the presence of the photoinitiator benzoin ethyl ether. Various parameters of the graft-copolymerization reaction, namely time, temperature, initiator, and monomer concentrations, were optimized using the grafting bath containing 10% methanol/acetone to dissolve the photoinitiator. The cotton sample, preswollen in sodium hydroxide, was subjected to grafting under optimized conditions. The preswollen sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Some researchers have successfully implanted PHEMA‐collagen (fibrillar) composite implants into bone (to the popliteal region of rats and to dog femurs) 15, 16. 2‐Hydroxyethyl methacrylate (HEMA), a vinyl monomer, is used as a coupling agent for natural fibers like jute, cotton, silk, etc 17–19. Fujiki et al20 used vinyl monomers as coupling agent for E‐glass fibers and found that graft copolymerization occurred from the surface of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have successfully implanted PHEMA‐collagen (fibrillar) composite implants into bone (to the popliteal region of rats and to dog femurs) 15, 16. 2‐Hydroxyethyl methacrylate (HEMA), a vinyl monomer, is used as a coupling agent for natural fibers like jute, cotton, silk, etc 17–19. Fujiki et al20 used vinyl monomers as coupling agent for E‐glass fibers and found that graft copolymerization occurred from the surface of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…15 The parameters of grafting were optimized by varying them so as to obtain maximum possible graft add-on along with maximum graft yield. Thus, 0.3% (w/v) BEE, 3 h, and 50°C were found to be the optimum conditions.…”
Section: Graft Copolymerizationmentioning
confidence: 99%
“…The graft copolymerization of varieties of monomers onto cellulose and cellulose derivatives has been carried out by different techniques such as irradiation with ultraviolet light (Shukla and Athalye 1992;Kubota et al 1995), gamma rays (Lu et al 2001), plasma ion beams (Sakata and Goring 1976) and by ceric (IV) ion initiation methods (Gurdag et al 2001;Gupta and Khandekar 2003). In these methods, the chain scission may occur and it is impossible to predetermine the length of the graft chains from the cellulose backbone because these methods are not controlled.…”
Section: Introductionmentioning
confidence: 99%